PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN SEKSUAL DALAM KAJIAN HUKUM ISLAM - Helen Intania Surayda (Universitas Semarang, 2017)
AbstractLegal protection for the interests of sexual violence victims either through the judicial process or by means of social care, is part of the legal policy. Thelegislation that becomes the reference for handling the sexual violence casesmakes it difficult for women to access justice. The elasticity of Islamic law ishighly adaptable to the dynamics of social change and the advance of the world.Multidimensional nature within the scope of Islamic law covers all aspects ofhuman life. The purpose of the establishment of Islamic law is to realize thebenefit for mankind. Just as the recovery of sexual violence victims is related tothe victim's invidual benefit. The problems in this thesis are: a) how legal protection for sexual violencevictims seen from positive law, b) how the legal protection for sexual violencevictims in the concept of Islamic law study. To answer the problems, researchwith juridical normative approach method with specification of analyticaldescriptive research is conducted. The type of data used in this research issecondary data. Based on the conducted research, it is found that protection for sexual violence victims have not been optimally facilitated by the state. The recovery of the violence victims must be broadly understood, not only in medical, legal or psycho-social interventions but also in the creation of situations in which the victims of violence can be fully empowered, so they are able to take decisions in their lives and are able to resume their roles in society as women and citizens.The law is always positive law, and the legal positivism lies on the fact that thelaw is created and abolished by human actions, so apart from the morality andthe norm systems themselves. The aspects of maslahah mursalah if applied to the legal protection for the victims of violence do not use normative approach as the case in general but the one which is used is the rights of the victims to takeprecedence in its handling.